Efektivitas Struktur Organisasi Badan Nasional Penanggulangan Terorisme Republik Indonesia - Yani Yuliani; Syamsul Maarif; Lukman M. Baga (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
The purpose of this research is to analyze the effectiveness of organizationalstructure. Based on the results of the analysis of the range of criteria for 62 respondents, it shows that the organizational structure of NCTA at the time of the study was quite effective. Three components of organizational structure, complexity, formalization, and centralization have a significant relationship with the effectiveness of the organizational structure. These results were obtained from the Spearman Rank correlation test. The results of the AHP showed that among the criteria, thecomplexity criterion was of the highest important and the alternative strategy that becomes the main priority is competency measurement.Keywords: Effectiveness of Organizational Structure; National Counter Agency AbstrakTujuan dari penelitian ini adalah untuk menganalisis efektivitas struktur organisasi. Berdasarkan hasil analisis rentang kriteria 62 responden menunjukkan bahwa struktur organisasi KNKT pada saat penelitian cukup efektif. Tiga komponen struktur organisasi, kompleksitas, formalisasi, dan sentralisasi memiliki hubungan yang signifikan dengan efektivitas struktur organisasi. Hasil ini diperoleh dari uji korelasi Rank Spearman. Hasil AHP menunjukkan bahwa diantara kriteria tersebut, kriteria kompleksitas merupakan yang paling penting dan alternatif strategi yang menjadi prioritas utama adalah pengukuran kompetensi.Kata Kunci: Efektifitas Struktur Organisasi; Badan Kontra Nasional